Characteristics of Wastes Produced by Polish Ferrous Alloys Casting Foundries between the Years 2010–2014 - Skrzyński, Mateusz (Journal of Casting & Materials Engineering, 2020)
The balance of wastes originating from the foundry processes of ferrous alloys, prepared on the basis of data made available by the Polish Central Statistical Office, is presented in this paper. The kind and amount of individual foundry wastes subjected to management and storage by foundry plants were analysed. The problem of wastes between the years 2010–2016 is discussed on the national scale, as well as in individual regions or voivodeships. Altogether, 27,375.9 tons of waste from the group no. 10, of which non-ferrous metal and ferrous alloy wastes from foundry plants constituted 2%, were produced in Poland in 2010. This situation remained at a similar level over successive years, till 2014. The positive prognosis constitutes the fact that the amount of waste stored on dumping grounds belonging to foundry plants in Poland is gradually decreasing. This may be related to increasing costs of waste storage. During the tested years, the annual amount of gathered waste decreased from 4,796.6 thousand tons (in 2010) to 4,477.6 thousand tons (in 2014).